2019
DOI: 10.1093/eurheartj/ehz110
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term outcomes of alcohol septal ablation for hypertrophic obstructive cardiomyopathy in patients with mild left ventricular hypertrophy: a propensity score matching analysis

Abstract: Aims Based on European guidelines, alcohol septal ablation (ASA) for hypertrophic obstructive cardiomyopathy (HOCM) is indicated only in patients with interventricular septum (IVS) thickness >16 mm. The aim of this study was to evaluate the short- and long-term outcomes in ASA patients with mild hypertrophy (IVS ≤ 16 mm). Methods and results We retrospectively evaluated 1505 consecutive ASA patients and used propensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Moreover, outcomes have been substantially less impressive outside of experienced centres, with an overall mortality of 5.2% in a nationally representative US database . ASA can have similar efficacy to myectomy, and may potentially be effective even for patients with minimal septal hypertrophy . Procedural mortality from ASA is ∼1%; however, it is associated with a 10–15% rate of complete heart block (CHB), repeat procedures, and a possible increased risk of scar‐related ventricular arrhythmias .…”
Section: Novel Procedural Techniques For Hypertrophic Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, outcomes have been substantially less impressive outside of experienced centres, with an overall mortality of 5.2% in a nationally representative US database . ASA can have similar efficacy to myectomy, and may potentially be effective even for patients with minimal septal hypertrophy . Procedural mortality from ASA is ∼1%; however, it is associated with a 10–15% rate of complete heart block (CHB), repeat procedures, and a possible increased risk of scar‐related ventricular arrhythmias .…”
Section: Novel Procedural Techniques For Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…70 ASA can have similar efficacy to myectomy, and may potentially be effective even for patients with minimal septal hypertrophy. 71 Procedural mortality from ASA is ∼1%; however, it is associated with a 10-15% rate of complete heart block (CHB), repeat procedures, and a possible increased risk of scar-related ventricular arrhythmias. 72,73 Moreover, ASA is dependent on coronary anatomy and, in one study, 15% of patients had unsuitable septal perforators.…”
Section: Novel Procedural Techniques For Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…It has been generally accepted that patients selected for ASA should be severely symptomatic and refractory to a medical therapy. [1][2][3] Some studies have suggested a positive prognostic outcome of septal reduction therapy (myectomy or ASA) when LVOT obstruction was eliminated. 6 Additionally, experienced centers have demonstrated a very low procedure-related mortality rate.…”
Section: Patient Selectionmentioning
confidence: 99%
“…It has been recently demonstrated that in selected patients, with both the modest septum thickness (15-16 mm) and with severe septal hypertrophy, ASA was found effective and safe in the long-term follow-up. 1,7 LVOT obstruction depends largely on the length of mitral leaflets and submitral chords, papillary muscle abnormalities including their number, hypertrophy, localization, and possible direct attachment to anterior mitral leaflet or short interposition of chords. Evidence suggests some patients encounter obstruction not only in LVOT but also in the midventricular part, therefore the precise evaluation of obstruction is necessary, and adding magnetic resonance imaging or computer tomography of a heart is very valuable.…”
Section: Anatomical Considerationmentioning
confidence: 99%
See 1 more Smart Citation